Exploring the Drivers, Challenges, and Opportunities of Supply Chain Technology Adoption for Small and Medium Enterprises (SMEs) in Malaysia - Abdul Rahman, Nor Azian; Abdul Rahim, Zulhasni (Information Management and Business Review, 2024)
Small and Medium Enterprises (SMEs) have a crucial impact on the Malaysian economy, making major contributions to the functioning of the supply chain. Integrating supply chain technology has become a crucial element in enhancing the efficiency and competitiveness of SMEs in Malaysia. During recent years many developing and developed countries have witnessed the expansion of markets and supply chain networks; in the progress of these market and supply systems SMEs find various complexities when they are implementing or improving the technology integration of their supply chain. The current body of literature often addresses the adoption of technology in a general manner or within larger organizations, resulting in a significant gap in study about the specific circumstances and requirements of small and medium-sized enterprises (SMEs). This study employs a rigorous methodology that analyzes relevant papers to examine the drivers, challenges, and opportunities for adopting supply chain technology among SMEs in Malaysia. By implementing supply chain technology, Malaysian SMEs can increase their performance in many areas of key performance indicators. This includes improving efficiency, optimizing inventory management, achieving cost savings, enhancing customer service, and increasing market competitiveness. It is believed that the findings of the study can be useful for managers of SMEs, policymakers, and interested stakeholders. This will enable SMEs to navigate the challenges of adopting technology more effectively and enhance global competitiveness.